Proceedings of the Evaluation and Assessment on Software Engineering 2019
DOI: 10.1145/3319008.3319018
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Evaluations on Software Testing Tools

Abstract: In software engineering practice, evaluating and selecting the software testing tools that best fit the project at hand is an important and challenging task. In scientific studies of software engineering, practitioner evaluations and beliefs have recently gained interest, and some studies suggest that practitioners find beliefs of peers more credible than empirical evidence. To study how software practitioners evaluate testing tools, we applied online opinion surveys (n=89). We analyzed the reliability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Rather, costs are categorized as a tool external factor [21]. In our prior research on tool evaluations [22], we found that practitioner evaluations for a tool, in a survey, may be dispersed. To improve understanding and robustness of the results, we analyze the topic using a complementary method.…”
Section: Related Workmentioning
confidence: 98%
“…Rather, costs are categorized as a tool external factor [21]. In our prior research on tool evaluations [22], we found that practitioner evaluations for a tool, in a survey, may be dispersed. To improve understanding and robustness of the results, we analyze the topic using a complementary method.…”
Section: Related Workmentioning
confidence: 98%
“…• To analyze what factors may influence the selection of software testing practices (Fernández-Sanz et al, 2009;Greiler et al, 2012;Pham et al, 2013;Pérez et al, 2013;Pfahl et al, 2014;Deak, 2014;Kochhar et al, 2015;Lima and Faria, 2016;Kochhar et al, 2019;Raulamo-Jurvanen et al, 2019). • To analyze software testing practices and the level of maturity in the industry (Fernández-Sanz, 2005;Grindal et al, 2006;Park et al, 2008).…”
Section: Related Workmentioning
confidence: 99%
“…Studies reported the gap between software testing state of the art and state of the practice (Ng et al, 2004;Dias-Neto et al, 2006;Sung and Paynter, 2006;Causevic et al, Software testing is still reported as a time consuming and expensive phase in software development (Beck and Perkins, 1983;Ng et al, 2004;Dias-Neto et al, 2006). The automation of software testing has continued its growth and there are opportunities for automated software testing research (Ghazi et al, 2015;Hynninen et al, 2018;Kochhar et al, 2019;Raulamo-Jurvanen et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, es fundamental realizar una revisión de estrategias encaminadas a agilizar los procedimientos de pruebas funcionales iterativas [10], en donde toma relevancia el concepto de automatización para aminorar la intervención de las personas en las actividades repetitivas, reduciendo el tiempo y esfuerzo requerido y aumentando la cobertura de los casos de pruebas [11], [12]. Dentro de la implementación de estrategias de pruebas en las organizaciones es recomendable integrar el software de automatización como herramienta de apoyo y contribución a la efectividad y calidad; algunos framework son el TestNG y JUunit y dentro de estos, es habitual usar herramientas como SeleniumHQ, Watir, Capibara y Cucumber, las cuales básicamente automatizan los navegadores a través de tareas que los usuarios podrían hacer en aplicaciones web [13], [14], [15] [16]; así como también se encuentra Robot Framework con el cual es posible realizar pruebas de aceptación y desarrollo, [17] y CodeceptJS que es de tipo E2E cuya visión es fundamentada en ambientes y desarrollo por comportamiento (BDD). [8], [18].…”
Section: Introductionunclassified